Intradialytic Stretching Exercise terhadap Nyeri dan Tekanan Darah pada Pasien Hemodialisis - Feni Novia; Dwiyanti Purbasari (STIKES Columbia Asia Medan, 2026)
Chronic Kidney Disease (CKD) is a global health problem with an increasing prevalence every year. CKD patients who undergo hemodialysis often experience complications such as muscle cramps, fatigue, and changes in blood pressure during the dialysis process that have an impact on quality of life. This study aims to analyze the effectiveness of the application of Intradialytic Stretching Exercise on pain and blood pressure in hemodialysis patients. The research method uses a qualitative approach with a case study design. The study sample consisted of one patient with a medical diagnosis of CKD on HD and a primary nursing diagnosis of chronic pain. Data were collected through nursing assessments including anamnesis, inspection, palpation, percussion, and auscultation. Implementation was carried out by administering Intradialytic Stretching Exercise according to the procedure, then evaluating the patient's pain level and blood pressure. Data analysis used comparative descriptive between pre- and post-intervention conditions. The research will be carried out in February 2026 at the Hemodialysis Room of Gunung Jati Hospital, Cirebon City. The results showed a decrease in pain scale, reduced muscle cramp complaints, patients appeared more relaxed, and blood pressure was stable during the hemodialysis process. These findings confirm that Intradialytic Stretching Exercise is effective as a nonpharmacological intervention to reduce pain and maintain blood pressure stability in hemodialysis patients.